Advancing systems and control research in the era of ML and AI. (2018) - Khargonekar, Pramod P.; Dahleh, Munther A.
Abstract: Fields of machine learning and artificial intelligence are undergoing transformative advances and growth. This article presents a vision for the field of systems and control that simultaneously leverages these advances to more fully engage with them and spur new expansive research directions in systems and control.